2020
DOI: 10.1007/s42729-020-00288-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Selenium on Serotonin Synthesis and the Glutathione Redox Cycle in Plum Leaves

Abstract: Selenium (Se), an essential micronutrient for humans, is also a beneficial nutrient for growth and development of many plants. The aim of the present study was to determine whether low-dose Se application could increase plum growth and serotonin synthesis, as well as upregulate the glutathione redox cycle. Two-year-old plum trees were treated with Se 6+ (Na 2 SeO 4) and Se 2− (SeMet). Growth parameters, levels of serotonin synthesis precursors, compounds and enzymes of the glutathione (GSH) redox cycle, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…As a result, the increase in tocopherols observed in our study could be attributed to increased DHAR activity [ 57 ]. Sun et al [ 58 ] previously demonstrated that Se increases the activities of ascorbate-glutathione cycle enzymes. The nanoparticles-mediated increased activities of these enzymes have been documented by the previous researchers [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the increase in tocopherols observed in our study could be attributed to increased DHAR activity [ 57 ]. Sun et al [ 58 ] previously demonstrated that Se increases the activities of ascorbate-glutathione cycle enzymes. The nanoparticles-mediated increased activities of these enzymes have been documented by the previous researchers [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Enzymes: GP, glycogen phosphorylase; G6Pase, glucose-6-phosphatase; HK, hexokinase; PFK, phosphofructokinase; PK, pyruvate kinase; G6PDH, glugose-6-phosphate dehydrogenase; LDH, lactate dehydrogenase; CS, citrate synthase; MDH, malate dehydrogenase regeneration of GSH from GSSG using NADPH (nicotinamide adenine dinucleotide phosphate) as an electron donor (Lushchak & Bagnyukova, 2006a;McCarthy, 2014). This de novo synthesis was likely activated by the increase in GST at the same exposure time in P. bifasciatus (Sun et al, 2020). Nonetheless, there was a reduction in GSH after 24 h of exposure, which could be explained by the liver being the main source of glutathione in vertebrates (Hermes-Lima, 2004;Nakano et al, 2014) that could have acted as a source of GSH to other organs.…”
Section: Enzymes and Biomarkers Of The Antioxidant Defence Systemmentioning
confidence: 99%
“…Se has also been related to the increase in the activity of other non-catalytic proteins, such as thioredoxin (TrxR) and protein P [ 114 ]. The impact of Se on antioxidant metabolites is associated with sulfur metabolism since both elements share uptake and assimilation pathways; the effects on the concentration of GSH and GSSH have been described in Allium [ 115 ] and Prunus domestica [ 116 ]. In species that can reach high concentrations of S, such as broccoli, the accumulation of glucosinolates is increased [ 117 ].…”
Section: Ronss In Plant Metabolismmentioning
confidence: 99%